Laryngomalacia: diagnosis and management at Otorhinolaryngology Head and Neck Surgery Department Dr.Soetomo Hospital, Surabaya - Muhtarum Yusuf; Puji Utami (Oto Rhino Laryngologica Indonesiana, 2020)
ABSTRACTBackground: Laryngomalacia is an abnormality of the larynx that leads to the inward collapse of the supraglottic structure during inspiration. The condition is primarily characterized by congenital stridor in infants and children. Diagnosis is often made based on the larynx visualization during inspiration. Laryngomalacia is generally recovers spontaneously at the age 2-5 years old, surgery is reserved for severe cases. Purpose: To obtain data of the clinical appearance, diagnosis, and therapy of laryngomalacia. Method: An observational study on medical records of all laryngomalacia patients at the Department of Otorhinolaryngology Head and Neck Surgery, Faculty of Medicine Universitas Airlangga /Dr. Soetomo General Hospital, Surabaya from January 1st, 2017 to December 31st, 2018. Data evaluation included clinical symptoms, type of laryngomalacia, comorbid factors, the age range of clinical improvement, and the management. Result: The main complaint of laryngomalacia was inspiratory stridor in 63 patients (82.89%), followed by dyspnea, snoring, hoarseness, and choking. Endoscopy finding mostly was type 1 in 69 patients (90.79%), the others were type 2 and 3. Comorbid factor mostly was neurological disease in 16 patients (21.03%), followed by congenital heart disease, congenital abnormality, prematurity, and laryngopharyngeal reflux. The age group of clinical improvement majority were <12 months, followed by >12-24 months, and no improvement in 56 patients (73.69%). Conservative therapy was conducted in 73 patients (96.05%) and 3 patients were tracheotomized. Conclusion: The main complaint of laryngomalacia was inspiratory noises, mostly found was laryngomalacia type 1.The highest comorbid factor was neurological disease. The most common management was conservative therapy. ABSTRAKLatar belakang: Laringomalasia adalah kolapsnya struktur supraglotik laring saat inspirasi. Laringomalasia umumnya sembuh spontan pada umur 2-5 tahun, pembedahan hanya dilakukan pada kasus yang berat.Tujuan: Memperoleh gambaran klinis penderita laringomalasia, diagnosis dan terapi. Metode: Penelitian observasional pada semua rekam medik yang lengkap penderita laringomalasia  di Departemen THT-KL RSUD Dr. Soetomo, Surabaya, periode 1 Januari 2017 - 31 Desember 2018. Data yang dievaluasi meliputi gejala klinik, tipe, faktor komorbid, usia perbaikan gejala, dan terapi. Hasil: Keluhan utama adalah napas berbunyi pada 63 penderita (82,89%), disusul sesak napas, mengorok saat tidur, suara parau, dan mudah tersedak. Temuan  endoskopik mayoritas tipe 1 pada  69 penderita (90,79%), sisanya tipe 2 dan 3. Faktor komorbid terbanyak penyakit neurologis pada   16 penderita (21,03%), disusul kelainan jantung bawaan, anomali kongenital, prematur, dan refluks laring faring. Usia perbaikan klinis mayoritas <12 bulan, diiikuti >12-24 bulan dan belum membaik 56 penderita (73,69%). Terapi konservatif dilakukan pada 73 penderita (96,05%) dan 3 penderita menjalani trakeotomi. Kesimpulan: Keluhan utama napas berbunyi, mayoritas laringomalasia tipe 1. Faktor komorbid terbanyak penyakit neurologis. Laringomalasia mayoritas diterapi secara konservatif.